Seed Morphology of Ten Common Aquatic Weeds of Transplanted Rice - I.C. BARUA; R. BORA; N.J. DAS; D.J. RAJKHOWA; N.T. YADURAJU; V.S.G.R. NAIDU; A. KUMAR (Seed Research, 2026)
Seed is one of the most important organs of weeds for persistence in the crop field. The importance of seed morphology is increasing along with the increasing interest on plant quarantine and soil seed bank. Seed morphology of ten most common weeds of transplanted rice viz., Aeschynomene indica, Cyperus iria, Echinochloa crmgalli, Ludwigia linifolia, Monochoria vaginalis, Oryza rufipogon, Paspalum scrobiculatum, Sacciolepis interrupta, Scirpus juncoides and Scirpus maritimus have been studied under 100 to 200 times magnification and measured with the help of software BIOPLSS-22 and ocular scale. Seed length of all the species, except O. rufipogon was less than 4 mm. Test weight (1000 seed weight) of the species, varied from 0.08 g (S. interrupta) to 10.00 g (A. indica). Presence of raphe in naked seeds of Z. linifolia separated the species from other species. Very prominent hilum was noticed only in A. indica and S. maritimus. The present findings on seed morphology were contribution for taxonomic operations of the weed flora and also were helpful in identifying seeds for plant quarantine activities, weed seed bank determination as well as for seed certification programmes.